Management of venous thromboembolism in patients with glioma. Issue 156 (August 2017) - Al Megren, Mosaad; De Wit, Carine; Al Qahtani, Mohammad; Le Gal, Grégoire; Carrier, Marc
Abstract: Background: Venous thromboembolism (VTE) is a common complication among patients with glioma. However, data on the safety of therapeutic doses of anticoagulation is scarce in this patient population. Objectives: The purpose of this study is to evaluate the risk of intracranial hemorrhage (ICH) in glioma patients receiving therapeutic anticoagulation for VTE treatment. Patients and methods: We conducted a case-control study including glioma patients with and without acute VTE from Jan 2010 to March 2015. Controls were matched based on age, gender and tumor grade. Result: 569 patients with glioma were identified, 76 (13.3%) developed acute VTE. Of the 70 patients treated with full dose anticoagulant therapy, 14 (20%) patients had a major bleeding including 11 (15.7%) ICH. The odds ratio for ICH in patients with glioma and VTE who were treated with anticoagulation compared to the control group was 7.5 (95% CI, 1.6–34.9) p = 0.01. Overall survival was similar for VTE and control group (36 vs. 42 months, p = 0.93). Conclusion: Therapeutic anticoagulation is associated with a 7-fold increase risk of ICH in glioma patients. Data emerging from this study support the need for high quality studies to evaluate the risk of ICH in patients with glioma and VTE. Highlights: Management of venous thromboembolism in patients with gliobastoma is challenging. The risk of intracranial bleeding is increased 7-fold on anticoagulant therapy. No significant predictor of the risk of bleeding could be identified.